2018
DOI: 10.20944/preprints201811.0179.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calorie Restriction Mimetics: Upstream-Type Compounds for Modulating Glucose Metabolism

Abstract: Calorie restriction (CR) has been shown to prolong the lifespan of humans, but enforcing long-term CR is difficult. Therefore, a compound that reproduces the effect of CR without CR is needed. In this review, we summarize the current knowledge on compounds with CR mimetic (CRM) effects. More than 10 compounds have been listed as CRMs, some of which are conventionally categorized as upstream-type CRMs showing glycolytic inhibition while the others are categorized as downstream-type CRMs that regulate or genetic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Of note, we do not directly demonstrate that in vivo 2-DG treatment reduces brain glycolysis after TBI. 2-DG is well established as an inhibitor of glycolysis (67) across multiple organ systems, animal models, and disease states (68)(69)(70)(71)(72)(73)(74)(75). We observe acute changes in blood glucose and ketone body levels (Figure 4, I-J) upon administration of 2-DG, consistent with 2-DG's ability to inhibit glycolysis and decrease glucose utilization.…”
Section: Discussionsupporting
confidence: 73%
“…Of note, we do not directly demonstrate that in vivo 2-DG treatment reduces brain glycolysis after TBI. 2-DG is well established as an inhibitor of glycolysis (67) across multiple organ systems, animal models, and disease states (68)(69)(70)(71)(72)(73)(74)(75). We observe acute changes in blood glucose and ketone body levels (Figure 4, I-J) upon administration of 2-DG, consistent with 2-DG's ability to inhibit glycolysis and decrease glucose utilization.…”
Section: Discussionsupporting
confidence: 73%
“…Thereafter, activation of SIRTs and autophagy (84) occur. It is considered that 2DG causes delay of age-related dysfunction, and shows effects similar to CR 85 . On some organisms it has been shown that 2DG can stimulate stress response proteins and heat shock protein 70 86 .…”
Section: Caloric Restriction Mimeticsmentioning
confidence: 99%
“…Increased breathing can induce the temporary upregulation of ROS, leading to increased anti-oxidative enzyme activity and survival rates. 16) 20) Orally administrated D-All also reduces body weight in rodents, 5) which might affect carbohydrate or lipid metabolism. However, the mechanism underlying the antiaging or antimetabolic effect of D-All is not precise, and the role of the nutrient sensor AMPK should be evaluated in the future.…”
Section: Methodsmentioning
confidence: 99%